Linear algebra-based solution of the gambler's ruin problem. Issue 1 (2nd January 2017) - Orosi, Greg
ABSTRACT: In this paper, we derive the result of the classical gambler's ruin problem using elementary linear algebra. Moreover, the pedagogical advantage of the derivation is briefly discussed.